20 years of British motorways proceedings of the conference held in London 27-28 February 1980. (Institution of Civil Engineers, 1980)
These papers focus on roads policy at different levels and the role of the motorways. As well as the contribution of research, the standards, specifications and design are discussed, and construction and maintenance. K. Clarke offers an opening address on the topic.